A GHEP-ISFG collaborative study on the genetic variation of 38 autosomal indels for human identification in different continental populations. (January 2018) - Pereira, R.; Alves, C.; Aler, M.; Amorim, A.; Arévalo, C.; Betancor, E.; Braganholi, D.; Bravo, M.L.; Brito, P.; Builes, J.J.; Burgos, G.; Carvalho, E.F.; et al.
Highlights: A collaborative study was performed by laboratories members of the GHEP-ISFG for a 38 autosomal indel multiplex. Allele frequency databases were created covering a comprehensive geographic area with representative samples from 21 different countries. Statistically significant differences were found among some admixed populations inside Latin America, namely in Brazil, Colombia and Mexico. The high levels of diversity found in all populations support the usefulness of this marker set in the forensic context. Abstract: A collaborative effort was carried out by the Spanish and Portuguese Speaking Working Group of the International Society for Forensic Genetics (GHEP-ISFG) to promote knowledge exchange between associate laboratories interested in the implementation of indel-based methodologies and build allele frequency databases of 38 indels for forensic applications. These databases include populations from different countries that are relevant for identification and kinship investigations undertaken by the participating laboratories. Before compiling population data, participants were asked to type the 38 indels in blind samples from annual GHEP-ISFG proficiency tests, using an amplification protocol previously described. Only laboratories that reported correct results contributed with population data to this study. A total of 5839 samples were genotyped from 45 different populations from Africa, America, East Asia, Europe and Middle East. Population differentiation analysis showed significant differences between most populations studied from Africa and America, as well as between two Asian populations from China and East Timor. Low F ST values were detected among most European populations. Overall diversities and parameters of forensic efficiency were high in populations from all continents.